A General Methodology for Beached Oil Spill Hazard Mapping - Sepp Neves, Antonio A.; Pinardi, Nadia; Navarra, Antonio; Trotta, F. (Frontiers in Marine Science, 2020)
The current lack of a standardized approach to computing the coastal oil spill hazard due to maritime traffic releases has hindered an accurate estimate of its global impact, which is paramount to manage and intercompare the associated risks. We propose here an hazard mapping approach that is based upon the methodology of ensemble simulations and the statistical analysis of the relevant distributions. Based on more than 20,000 ensemble simulations of oil spills from maritime traffic routes, we demonstrate that beached ocean tracer concentration distributions fit a Weibull curve, a two-parameter fat-tail probability distribution function. Two indicators that quantify the coastal oil spill hazard are proposed and applied to the Algarve coast, Portugal.